Innovations in Nursing Interventions for Chronic Disease Management: A Comprehensive Review - Khawlah Ahmed Alali et al. (International Journal of Scientific Research and Innovative Studies, 2024)
The growing rate of chronic diseases is one of the most prominent threats in healthcare today; therefore, ensuring that successful methodological approaches are developed for the prevention, care, and management of chronic diseases remains a priority. Chronic illnesses constitute a significant aspect of day-to-day practice for nurses as the primary healthcare professionals for patients with such conditions through guardianship, teaching, coordination, and applying research findings. Primary sources include peer-reviewed articles and books published over the last five years to address recent advancements in nursing interventions within chronic illness management and areas of interest such as telehealth, digital health, artificial intelligence precision nursing, and genomic medicine. Based on the evaluated studies and academic findings, this review focuses on the ability of these interventions, when applied, to improve patient addresses and the overall quality of care. However, the review informs on the various issues surrounding incorporating advanced technologies in nursing, including the hurdles, ethical dilemmas, and disparities affecting the health system. In doing so, this review seeks to enhance a more profound appreciation of the contemporary dynamics of nursing practice regarding chronic diseases so that stakeholders at various levels of the healthcare delivery chain can continue not only to be equipped with the requisite knowledge, skills, and resourcefulness to effectively charger the rising tide of chronic diseases, but also to rise to the challenge that comes with this emerging healthcare trend. Keywords: Long-term conditions, Enabling care, Remote consultancy, E-health, Artificial intelligence, Personalized care, Pharmacogenomics, Innovation, Technology, Patient Experience, System dynamics. Received Date: September 13, 2024 Accepted Date: October 11, 2024 Published Date: November 10, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/196 DOI: https://doi.org/10.5281/zenodo.14062599